Some reflections on race and racism in Brazil - Mayorga, Claudia (Revista Pesquisas e Práticas Psicossociais, 2017)
In this paper we propose a course of analysis aimed at the clarification of how racism and racial inequality have been shaped, naturalized and institutionalized in Brazil based on specificities strongly linked to the dynamics of Brazilian society from, among others, the viewpoint of the interests of the elite, the colonial rationale, and the process of modernization of the Brazilian State. We first analyze the process of invention of races in the West and the scientific racism in Brazil until the development of the myth of racial democracy. Then, we highlight the contributions of the black movement that have been fundamental to the acknowledgement of racial equality as a public issue in Brazil. Keywords: racism; racial democracy; Brazil; black movement.